Student violence in the university community: a psychosocial approach - FARES, Zahra; LAMRI, Abdelouahab (Journal of Human Sciences, 2020)
This study aimed at examining the phenomenon of student violence at the Algerian university, as it is considered one of the frequent phenomena in institutions of higher education, especially in recent times, as it has become one of the growing problems, that haunt the university family, Which requires researchers and interested customers to pay attention to the phenomena of violence in its various forms. The study also aimed at approaching violence in the university community, psycho-social approach, by displaying the concept of violence and university violence, and the factors that cause it with exposure to the most important approaches that explained the phenomenon.